Formed aggregate reinforcement for concrete
Molded aggregate particles with increased surface area features, such as fins and hollow cores, improve the molecular interactions with cement particles, addressing the challenge of enhancing the mechanical strength and bonding of concrete materials.
Patent Information
- Application Number
- JP2024556431
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-01-06
- Filing Date
- 2023-03-21
- Publication Date
- 2025-04-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Certain plastics, when incorporated into cement to produce concrete, exhibit lower energy molecular interactions with cement particles, leading to a stronger interface and potentially more robust concrete material, but existing designs often lack features that maximize surface area and interfacial interactions.
The use of molded aggregate particles with regular shapes and additional features that increase surface area, such as fins, ribs, and hollow cores, distributed within a cement mixture to enhance molecular interactions and mechanical properties of the concrete.
The increased surface area of the molded aggregate particles leads to better adhesion with cement particles, resulting in improved mechanical strength and potential bonding numbers, thereby enhancing the overall performance of the concrete material.
Smart Images

Figure 2025510131000001_ABST
Abstract
Description
[Technical field]
[0001] cross reference This application claims priority to U.S. Provisional Patent Application No. 63 / 322,193, entitled "Shaped Aggregate Reinforcements for Concrete," filed March 21, 2022, and U.S. Provisional Patent Application No. 63 / 478,873, entitled "Shaped Aggregate Reinforcements for Concrete," filed January 6, 2023, each of which is incorporated by reference in its entirety.
[0002] The present disclosure generally relates to shaped aggregate particles and reinforcement for concrete. Specifically, but not limited to, the present disclosure relates to plastic shaped aggregate particles. Plastic shaped aggregate particles can be made from recycled plastics. Such shaped aggregate particles can contain recycled and non-recycled glass fibers and particles, silica, or similar materials, and / or combinations. Morphology of shaped aggregate particles includes, but is not limited to, spherical particles, helical structures, elongated ellipsoids, fibers, interlocking structures, spherical burst patterns, or similar structures such as tetrahedrons, rectangular prisms, and pyramids. The shaped aggregate particles can be made from recycled plastic waste and can be used with and without similar materials such as discontinuous glass fibers and / or chopped glass fibers and glass particles for use in concrete applications as fillers and supports. [Background technology]
[0003] Aggregates in concrete are used as fillers and to increase the mechanical strength of the final concrete product (Non-Patent Documents 1-3). Standard aggregates for concrete are made from stone and crushed stone, and more than 48.3 billion tons of aggregates were used in 2015 alone (Non-Patent Documents 1-3). Meanwhile, societal use of plastics is increasing, with an estimated 313 million tons of plastics generated in 2014 and 59 million tons of plastic waste disposed of in the same year. Unfortunately, recycling is not a complete solution, with only 8.9% of plastic waste being recycled in the United States in 2012, and the majority of plastics being sent to landfills (Non-Patent Documents 1-3).
[0004] As a potential non-recycling "reuse" solution, non-recyclable plastics can be incorporated into concrete as aggregates (Non-Patent Documents 1-5), and the incorporation of recycled plastic aggregates can provide beneficial properties or improve existing properties of concrete materials. For example, a study by Choi et al. noted that when spherical, smooth-surfaced waste plastic polyethylene terephthalate (PET) aggregates were used in concrete at a 75% replacement level, the slump increased by 46% compared to standard concrete (Non-Patent Document 5). A study by Mohammed et al. found that plastic aggregates derived from PVC sheets could be incorporated into concrete at a replacement rate of 30% without significantly affecting the strength of the concrete (Non-Patent Document 3). Furthermore, the researchers found that PVC exhibited a relatively good size distribution effect compared to other plastics. Another study by Alqahtani et al. showed that concrete containing manufactured plastic aggregates exhibited post-peak ductile behavior at 25% replacement (Non-Patent Document 4). Therefore, this type of concrete containing mixed plastic aggregates can be used for structural and non-structural applications that require reasonable strength and ductility (Non-Patent Documents 1-5).
[0005] Plastic aggregates can be incorporated into concrete in the form of chopped, shredded, or formed plastic, but most designs utilize chopped plastic or plastic pellets, which can be round, elliptical, or roughly cylindrical (Non-Patent Documents 1-7). For example, Arqlite SmartGravel™ utilizes recycled plastic as aggregate in the shape of a rounded cylinder, with a smooth surface and no additional surface features or features (Non-Patent Document 8). [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] Saikia, Nabajyoti, and Jorge De Brito. "Use of plastic wasteas aggregate in cement mortar and concrete preparation: A review." Construction and Building Materials 34 (2012): 385-401. [Non-Patent Document 2] Ismal, iZainab Z., and Enas A. Al-Hashmi. "Use of waste plastic in concrete mixture as aggregate replacement." Waste management 28 .11 (2008): 2041-2047. [Non-Patent Document 3] Mohammed, Azad A., Ilham I. Mohammed, and Shuaaib A. Mohammed. "Some properties of concrete with plastic aggregate derived from shredded PVC sheets." Construction and Building Materials 201 (2019): 232-245 [Non-Patent Document 4] Alqahtani, Fahad K., et .al. "Novel lightweight concrete containing manufactured plastic aggregate." Construction and Building Materials 148 (2017): 386-397. [Non-Patent Document 5] Choi, Yun-Wang, et .al. "Effects of waste PET bottles aggregate on the properties of concrete." Cement and concrete research 35.4 (2005): 776-781. [Non-Patent Document 6] Basha, Shaik Inayath, et al. "Mechanical and thermal properties of lightweight recycled plastic aggregate concrete." Journal of Building Engineering 32 (2020):101710. [Non-Patent Document 7] Sambhaji, Patil Pramod. "Use of waste plastic in concrete mixture as aggregate replacement." International Journal of Advanced Engineering Research and Science 3.12 (2016): 236956. [Non-Patent Document 8] https: / / www.arqlite.com / site / construction Summary of the Invention [Problem to be solved by the invention]
[0007] Certain plastics, when incorporated into cement to create concrete, have lower energy molecular interactions with the cement particles, increasing the likelihood of a stronger interface in the final concrete material. As a result, certain plastics, namely PVC, HDPE, epoxies, polyesters, and nylons, are suitable for incorporation into cement as aggregates to create concrete and will exhibit stronger interactions with the surrounding cement matrix, resulting in an overall stronger concrete material. [Means for solving the problem]
[0008] In a first aspect, the present disclosure provides a composition comprising a plurality of shaped aggregate particles distributed within a mixture of cement, each shaped aggregate particle comprising a regular shape having one or more features that provide additional surface area, and the shaped aggregate particles comprising a plastic.
[0009] In a second aspect, the disclosure provides a method for producing concrete, the method comprising mixing a plurality of shaped aggregate particles with a cement mixture, the cement mixture comprising cement and one or more additional ingredients.
[0010] Further aspects and embodiments are provided in the preceding drawings, detailed description, and claims.
[0011] The following drawings are provided to illustrate certain embodiments described herein. The drawings are merely exemplary and are not intended to limit the scope of the claimed invention, nor are they intended to show every possible feature or embodiment of the claimed invention. The drawings are not necessarily drawn to scale, and in some instances, certain elements of the drawings may be enlarged relative to other elements of the drawings for illustrative purposes. [Brief description of the drawings]
[0012] [Figure 1]1 depicts a spherically shaped aggregate particle with a tapered design where the fins meet at a single point at the north and south poles of the sphere. [Diagram 2] 1 depicts a spherically shaped aggregate particle with a tapered design where the fins meet at a single point at the north and south poles of the sphere. [Diagram 3] 1 depicts a spherical shaped aggregate particle having an offset design with more ribs on the outside and a hollow core intersected by ribs extending from the north and south poles. [Figure 4] 1 depicts a spherical shaped aggregate particle having protrusions from the center of the sphere. [Diagram 5] 1 depicts a spirally shaped aggregate particle. [Figure 6] 1 depicts aggregate particles produced by extrusion. [Figure 7] 1 depicts aggregate particles produced by extrusion and shaped through cutting the extrusion. [Figure 8] 1 depicts aggregate particles produced by extrusion and cutting at different temperatures. [Figure 9] Depicts a two-dimensional woven fabric structure. [Figure 10] Depicts a three-dimensional woven fabric structure. [Figure 11A] 1 depicts a side view of a cement paver having plastic molded aggregate particles with a rectangular geometry with rounded corners to offset angular stresses. [Figure 11B] 11B depicts the top surface of the cement paver of FIG. 11A. [Figure 12] 1 depicts woven aggregate within poured concrete. [Figure 13] The interlocking ring aggregate particles are depicted. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The following description lists various aspects and embodiments of the invention disclosed herein. The specific embodiments are not intended to define the scope of the invention. Rather, the embodiments provide non-limiting examples of various compositions and methods that fall within the scope of the claimed invention. The description should be read from the perspective of a person skilled in the art. Thus, it does not necessarily include information that is known to a person skilled in the art.
[0014] definition The following terms and phrases have the meanings set forth below unless otherwise specified herein. This disclosure may use other terms and phrases not expressly defined herein. Such other terms and phrases shall have the meanings that they would have within the context of this disclosure to a person of ordinary skill in the art. In some cases, a term or phrase may be defined in the singular or plural. In such cases, it is understood that any term in the singular may include its plural counterpart and vice versa, unless expressly stated to the contrary.
[0015] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. For example, reference to a "substituent" includes a single substituent, as well as two or more substituents, and the like.
[0016] As used herein, "for example," "for instance," "such as," or "including" are meant to introduce examples that further clarify a more general subject matter. Unless expressly indicated otherwise, these examples are provided only as an aid in understanding the embodiments illustrated in this disclosure and are not intended to be limiting in any way. Additionally, these phrases do not imply any kind of preference for the disclosed embodiments.
[0017] The present disclosure provides disclosure for new shaped aggregate particles. In embodiments, the shaped aggregate particles include regular shapes and one or more features in addition to the regular shapes that provide additional surface area to the regular shapes.
[0018] As used herein, "shaped" refers to a consistent geometric shape with less than 5% particle-to-particle variation between particles of the same "shaped". Thus, "shaped" refers to a non-random morphology that is selected to have a specific geometric shape.
[0019] As used herein, a "regular shape" is a geometric shape that forms the overall impression of an aggregate particle. Examples of "regular shapes" include, but are not limited to, spheres, cylinders, rods, cones, cubes, cuboids, pyramids, prisms, regular and irregular polyhedrons, helices, closed helices, open helices, spirals, tori, ellipsoids, elongated ellipsoids, spherical bursts, stars, and fibers.
[0020] As used herein, a "feature" is an alteration to a regular shape that increases the surface area of the regular shape. Thus, a "feature" can be a cavity or void on the surface of the regular shape, including voids that pass completely through the regular shape, protrusions or other bodies on the regular shape that serve to increase the surface area. Examples of "features" include, but are not limited to, fins, ribs, twists, bends, ridges, valleys, hollow cores, and weaves.
[0021] The shaped aggregate particles may be formed by injection molding, compression molding, weaving, pultrusion, extrusion, 3D printing, knitting, or may be produced through similar methods. In embodiments, the shaped aggregate may include plastic. In certain embodiments, the plastic may be recycled plastic.
[0022] The plastic can be any plastic or combination of plastics. The combination of plastics can contain only virgin plastics, only recycled plastics, or a combination of virgin and recycled plastics. In certain embodiments, the plastic can be selected from PVC, HDPE, polyester / PET, epoxy, and nylon, and combinations thereof. The plastic can further contain additives, fillers, stabilizers, and / or similar materials.
[0023] In certain embodiments, the shaped aggregate particles may contain up to 100% plastic. Certain shaped aggregate particles may contain about 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 45%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 100% plastic by volume. The shaped aggregate particles may contain at least 65% plastic. The shaped aggregate particles may contain at least 75% plastic. The shaped aggregate particles may contain about 65% to about 75% plastic.
[0024] In certain embodiments, the shaped aggregate particles may further comprise glass fibers, discontinuous glass fibers, glass particles, silica, or any combination thereof. The glass fibers, discontinuous glass fibers, glass particles, and silica may range in size from 100 μm to 100 mm. The glass fibers, discontinuous glass fibers, glass particles, and silica may all be substantially the same size, or may be a number of different sizes in any particular aggregate particle. In embodiments, the size of the particles may be about 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, or 100 mm. The incorporation of glass fibers, discontinuous glass fibers, glass particles, silica, or any combination thereof may provide increased mechanical strength, an increased number of potential bonds with cement binders, as well as other benefits to the shaped aggregate particles.
[0025] In certain embodiments, the shaped aggregate particles may comprise up to 80% by volume of glass fiber, discontinuous glass fiber, glass particles, silica, or any combination thereof. Certain shaped aggregate particles may comprise approximately 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, or 80% by volume of glass fiber, discontinuous glass fiber, glass particles, silica, or any combination thereof. The shaped aggregate particles may comprise at least 25% silica. The shaped aggregate particles may comprise at least 35% silica.
[0026] The shaped aggregate particles may be in the form of spherical particles, helical structures, elongated ellipsoids, fibers, interlocking structures, and spherical burst patterns, or similar structures. The spherical aggregate particles may incorporate finned and / or ribbed features to impart a much greater surface area compared to conventional spherical aggregate particles. The inventors have shown through specific compositions and engineering that shaped aggregate particles can be successfully incorporated into cement to create a viable concrete material.
[0027] The spherical aggregate particles may be generally spherical and may be approximately 1 mm to 50 mm in diameter. Particular spherical aggregate particles may be approximately 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm, 45 mm, or 50 mm in diameter.
[0028] The spherical aggregate particles may include features such as various fin structures extending from the north and south poles of the spherical particle, and the number of fins may vary depending on the size of the shaped aggregate particle.
[0029] Smaller spherical aggregate particles, such as in Figures 1 and 2, may have a tapered design that meets at a point at the north and south poles of the sphere. Figure 1 depicts a spherical aggregate particle that includes eight longitudinal fins, such as fin 1. The longitudinal fins meet at both poles, such as north pole 3. In addition, the aggregate particle includes an equatorial fin 5 that circles the aggregate particle midway between the poles. The arrangement of the fins creates spaces between them, such as space 7. The spaces allow for the infiltration of cement.
[0030] 2 depicts a spherical aggregate particle including twelve longitudinal fins, such as fin 201. The longitudinal fins meet at poles, such as north pole 203. In addition, the aggregate particle includes an equatorial fin 205 that circles the aggregate particle midway between the poles. The arrangement of the fins creates spaces between them, such as space 207.
[0031] Larger plastic molded aggregate particles may have an offset design with more ribs on the outside and a hollow core intersected by ribs extending from the north and south poles. Figure 3 depicts a spherical aggregate particle with eight longitudinal fins, such as fin 301, that meet at both poles, such as north pole 303. In addition, the aggregate particle includes an equatorial fin 305 that circles the aggregate particle midway between the poles. In addition, latitudinal fins, such as latitudinal fin 209, circle the aggregate particle between the equatorial fins and the poles. The arrangement of the fins creates spaces between them, such as space 207.
[0032] The fins, and the spaces between them, offer several advantages over other plastic aggregate designs, namely smooth spherical, elliptical, and cylindrical shapes, in terms of surface area and potential interfacial interactions. For example, a 10 mm spherical finned aggregate particle significantly increases its surface area compared to smooth surface designs, with the spherical finned aggregate particle having a surface area of 608 mm. 2 and a standard smooth sphere has the same volume (343 mm 3 ) 236.97 mm 2 Thus, the surface area of the engineered finned plastic aggregate particles can be more than twice the surface area of a sphere having the same volume and diameter. The increased surface area of the finned plastic aggregate particles allows for greater potential molecular interactions with the cement particles in the concrete, allowing for better adhesion. In embodiments, the regular shaped aggregate particles having the features described herein can have an increased surface area compared to aggregate particles of the same regular shape but lacking a feature. In certain embodiments, the regular shaped aggregate particles having the features described herein have an increased surface area ratio of at least 1.2 times, at least 1.5 times, at least 2 times, at least 2.2 times, or at least 2.5 times compared to aggregate particles of the same regular shape but lacking a feature.
[0033] Larger aggregates often result in a deterioration of the strength of the concrete material and a reduction in compressive strength. As an additional measure to combat this, the aggregate particles described herein may incorporate a hollow design to provide reinforcement. Specifically, larger shaped aggregate particles, such as plastic shaped aggregate particles with diameters of 10 mm or more, may contain a hollow core (e.g., FIG. 3), allowing the cement to act as a reinforcement for the larger aggregate particles by allowing the cement to pass completely through the particle. This also provides additional surface area for interfacial interaction with the cement while also providing a reinforcing effect.
[0034] The shaped aggregate particles or burst patterns or similar designs may include spherical, ellipsoidal, or similar regular shapes with multiple protruding features, providing increased surface area compared to a standard sphere. Figure 4 depicts a shaped particle with a spherical base 411 and cylindrical protrusions 413. The protruding features may be any shape or size, such as cylinders, knobs, cones, etc.
[0035] The spiral aggregate particles, or similar designs, can be closed spirals or open spirals. In embodiments such as FIG. 5, the spiral aggregate particles are 10-25 mm in length. Particular spiral aggregate particles can be about 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, 21 mm, 22 mm, 23 mm, 24 mm, or 25 mm in length. In embodiments, the spiral aggregate particles are 1-10 mm in diameter. Particular spiral aggregate particles can be about 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or 10 mm in diameter. In particular embodiments, the spiral aggregate particles are closed spirals enclosing a hollow interior space.
[0036] Other particle shapes can be produced, including teeth, sails, S-shapes, trefoils, laminated shapes, spheres with projections, cubes, dumplings, lumps, and beads, as seen in Figures 6-8. Many of these shapes are formed through the extrusion and cutting of the extruded fibers.
[0037] The shaped aggregate particles may include plastic fibers. Such plastic fibers may be rods of various shapes, including cylindrical, triangular, rectangular, or hexagonal. In embodiments, such plastic fibers may be about 1 to about 1,000 mm in length. Particular plastic fibers may be about 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm, 45 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, 100 mm, 200 mm, 300 mm, 400 mm, 500 mm, 600 mm, 700 mm, 800 mm, 900 mm, or 1000 mm in length. In embodiments, such plastic fibers may be about 1 to about 100 mm in diameter. Certain plastic fibers may be about 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm, 45 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, or 100 mm in diameter.
[0038] In certain embodiments, the plastic fibers may further include glass fibers, discontinuous glass fibers, glass particles, silica, or any combination thereof. The glass fibers, discontinuous glass fibers, glass particles, and silica may range in size from 100 μm to 100 mm. The glass fibers, discontinuous glass fibers, glass particles, and silica may all be substantially the same size, or may be a number of different sizes in any particular aggregate particle. In embodiments, the size of the particles may be about 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, or 100 mm. The incorporation of glass fibers, discontinuous glass fibers, glass particles, silica, or any combination thereof may provide increased mechanical strength, an increased number of potential bonds with cement binders, as well as other benefits to plastic fibers.
[0039] In certain embodiments, the plastic fibers may comprise up to 80% by volume of glass fibers, discontinuous glass fibers, glass particles, silica, or any combination thereof. Certain shaped aggregate particles may comprise approximately 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, or 80% by volume of glass fibers, discontinuous glass fibers, glass particles, silica, or any combination thereof. The plastic fibers may comprise at least 25% silica. The plastic fibers may comprise at least 35% silica.
[0040] In an embodiment, shaped aggregate particles and / or plastic fibers of various sizes, especially those with hollow structures, or similar designs, may be interlocked together to create a continuous structure and then incorporated into concrete to improve the tensile strength of the concrete material.
[0041] Further disclosed herein are shaped aggregate particles in the form of a fabric structure in the form of a woven mat, in either 2D or 3D form, which may provide additional benefits to concrete, namely improved tensile strength, impact resistance, and flexibility.
[0042] The first weave structure may consist of a 2D woven fabric structure. The fabric structure may include any of the plastic fibers mentioned above. These 2D woven fabric structures may include two-dimensional weave patterns. Examples of weave patterns include, but are not limited to, plain weave, twill weave, satin weave, triaxial weave, stitch weave, basket weave, or other weave designs. These woven fabric structures may be incorporated into concrete individually or as layers to form plies (e.g., FIG. 6). Welt tows, warped tows, or z-tows may be fully composited with the aforementioned plastic fibers. The woven fabric structure may further include reinforcement, for example, glass fiber tows.
[0043] The welted tows, warped tows, or z-tows, in any combination thereof, may be cylindrical or flat with a diameter of 1 mm to 100 mm and a length of 1 mm to 10 m. In certain embodiments, the welted tows, warped tows, and / or z-tows may be 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, or 100 mm in length. In combinations, the welted tows, warped tows, and / or z-tows may be 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or 10 mm in diameter.
[0044] Further disclosed are three-dimensional (3D) textile structures, such as the example shown in Figure 7. Such 3D textile structures may include the same or similar material compositions as the 2D structures. In specific embodiments, the 3D textile structures may include the described plastic fibers and may additionally include one or more reinforcing fiberglass tows. Through thickness (TT) interlocking structures may include all welts, warps, and binders made from the described plastic fibers, in addition to separate fiberglass tows, or combinations thereof.
[0045] 2D or 3D recycled plastic woven structures can be hand woven, woven over a mandrel, 3D printed, or constructed using similar methodologies to create variations on the shapes listed above.
[0046] By adding either 2D or 3D woven fabric to concrete, the strength of concrete, as well as the tensile, toughness, and deformation performance of concrete can be improved. The concrete structure containing the above-mentioned recycled plastic 2D or 3D woven structure can exhibit improved flexural strength due to the high elastic modulus of plastic fibers, allowing concrete to be used in applications where frequent loads are observed, such as walkways, roads, highway barriers, sidewalks, and roadways.
[0047] Woven structures may also be integrated in the form of continuous or discontinuous fibers, or as non-woven structures or discontinuous fibers integrated into a fabric or similar structure, which may improve the crack resistance of the final concrete structure.
[0048] Additionally, plastics can be printed as individual layers for use as either 2D or 3D shaped aggregate particles that can be incorporated into concrete as fillers, 3D printing applications, or similar applications. These structures can be fabricated using injection molding, 3D printing, or similar methods. The individual layers can then interlock together through interlocking posts that can be fitted into subsequent layers, or the individual layers interlock together the weave of the structure itself.
[0049] The plastic molded aggregate particles can be incorporated into products such as concrete, walkways, pavers, or pavers that can be molded, precast, 3D printed, handcrafted, or made using similar techniques. Specifically, as shown in Figures 8 and 9, cement pavers with molded aggregate particles can have a rectangular geometry with rounded corners to offset corner stresses. The sides can be straight or slightly tapered to give a more rounded geometry, as shown in Figure 8. The top corners can have more rounded corners compared to the bottom corners, tapering slightly from top to bottom. Additionally, these pavers can include a logo (e.g., MAA'VA) or pattern on the top, or can have an unfinished surface.
[0050] While the specific dimensions and geometries are described as potential best embodiments, additional sizes and shapes may be used.
[0051] Various plastics, plastic combinations, and other materials have different temperature response characteristics. Different choices may be appropriate in applications having different environmental conditions, such as fire risks, extreme temperature fluctuations, extreme cold, etc.
[0052] While the use of a wide variety of shaped aggregate particles is common, the inventors have made the distinction of specifically optimizing the shape (geometry) and spatial distribution (including interlocking) of the shaped aggregate particles.
[0053] The inventors note that the examples of specific sizes, size ranges, shapes, and materials represent an understanding of preferred embodiments of the invention, and the inventors contemplate that variations in shapes, sizes, and materials may be used in different circumstances.
[0054] The inventors further note that these techniques may be used synergistically with carbon dioxide injection or other carbon sequestration techniques.
[0055] In the process of concrete preparation, these shaped aggregate particles may be mixed into the cement randomly or in a specified order. The shaped aggregate particles may be of a uniform type or may include a plurality of regular shapes, forms, and / or sizes.
[0056] Thorough mixing of the cement can be used to provide a uniform distribution of shaped aggregate particles in the cement. In the case of spherical, burst, spiral, and elliptical plastic shaped aggregate particles, or similar designs, this mixing effect can also increase the likelihood that the concrete will exhibit isotropic properties, as the shaped aggregate particles are stochastically distributed throughout the mixture. This can increase the likelihood that the resulting concrete will exhibit a more uniform distribution of mechanical properties.
[0057] In embodiments, the shaped aggregate particles may be mixed with the cement to an extent that the shaped aggregate particles comprise about 10% to about 25% (w / w), or about 10% to about 50% of the resulting mixture. In certain embodiments, the shaped aggregate particles may comprise about 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 30%, 35%, 40%, 45%, or 50% (w / w) of the resulting mixture.
[0058] In an embodiment, one or more of CaOH, CO2, sand, silica by-products, and / or water may be mixed with the cement and shaped aggregate particles. The mixture including the cement and shaped aggregate particles may then be formed into a final shape before hardening to form concrete.
[0059] Further described herein is a concrete comprising shaped aggregate particles and cement. In certain embodiments, the shaped aggregate particles may be randomly distributed throughout the concrete. In other embodiments, the shaped aggregate particles may be present in the concrete in a defined distribution or location. The shaped aggregate particles may be of a uniform type or may include a plurality of regular shapes, forms, and / or sizes.
[0060] In embodiments, the shaped aggregate particles comprise about 10% to about 25% (w / w) of the concrete, or about 10% to about 50%. In certain embodiments, the shaped aggregate particles can be about 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 30%, 35%, 40%, 45%, or 50% (w / w) of the concrete.
[0061] In an embodiment, the concrete further comprises one or more of CaOH, CO2, sand, silica by-products, and / or water. In an embodiment, the concrete is formed / shaped prior to curing. For example, the concrete may be formed into one or more of bricks, pavers, countertops, sinks, wall slabs, floor slabs, barricades, coffee tables, household items such as candlesticks and bowls, and lighting elements made of concrete. In an embodiment, the concrete is in the form of a walkway material. In a further embodiment, the walkway material is a paver. In yet an additional embodiment, the paver comprises one or more characteristics selected from the group consisting of rectangular geometry, rounded geometry, rounded corners, straight sides, tapered sides, and a logo embedded or imprinted on the paver surface.
[0062] The cements described herein may have a compressive strength of at least 1300 PSI. In certain embodiments, the cements may have a compressive strength of at least 100 PSI, 200 PSI, 300 PSI, 400 PSI, 500 PSI, 600 PSI, 700 PSI, 800 PSI, 900 PSI, 1000 PSI, 1100 PSI, 1200 PSI, 1300 PSI, 1400 PSI, 1500 PSI, 1600 PSI, 1700 PSI, 1800 PSI, Having a compressive strength of 1900 PSI, 2000 PSI, 2500 PSI, 3000 PSI, 3500 PSI, 4000 PSI, 4500 PSI, 5000 PSI, 5500 PSI, 6000 PSI, 6500 PSI, 7000 PSI, 7500 PSI, 8000 PSI, 8500 PSI, 9000 PSI, 9500 PSI, or 10000 PSI. EXAMPLES
[0063] The present invention is further described in the following examples, which are provided by way of illustration and are not intended to limit the invention in any way.
[0064] Example 1. Preparation of plastic-silica molded aggregate particle spheres. Virgin nylon 6 plastic was molded into spherical aggregate particles. The finned spheres were designed to maximize the inner and outer surface area. The inner surface of the finned spheres is close to the outer surface. For molding, virgin nylon 6 (Formlabs) was prepared by mixing nylon 6 with silica (integrated, 10-500 micron suspended silica) in a nylon:silica ratio of 65%:35%. Nylon-silica mixtures were prepared using liquid nylon with suspended silica, which was mixed for 10 minutes. The prepared plastic was molded via 3D printing [100 micron print resolution at 30°C, standard pressure, and chemical post-cure] (Formlabs Form 3BL) into finned spheres with diameters of 0.5 mm (Figure 1), 7.5 mm (Figure 2), and 10 mm (Figure 3).
[0065] Finned spheres were also fabricated by melting nylon 6 at 200-400°C until it became viscous, incorporating 10-500 micron silica into the molten mixture, and stirring for 20 minutes until it became homogeneous. The nylon 6 with suspended silica was molded via injection molding using a die cast mold into finned spheres with diameters of 0.5 mm (Figure 1), 7.5 mm (Figure 2), and 10 mm (Figure 3).
[0066] Example 2. Preparation of plastic-silica shaped aggregate particles. Plastic-silica aggregate particles may also be fabricated by melting nylon 6 at 300-400°C until viscous, incorporating 10-500 microns of silica into the molten mixture, and stirring for 20 minutes until homogenous. The nylon 6 with suspended silica was then formed into plastic-silica shapes via extrusion at 200-400°C. FIG. 6 is an extrusion method for producing aggregate particles. The plastic-silica was extruded and a section cut from the extrusion. In some embodiments, aggregate particle 623 is tooth-shaped or arch-shaped. In some embodiments, aggregate particle 625 is flag-shaped. In some embodiments, aggregate particle is S-shaped or hook-shaped. These shapes are produced when the plastic is extruded and cooled before cutting. Cooling the plastic before cutting provides defined sides and edges. Aggregate particle 731 in FIG. 7 includes an upper pyramid portion 733 that may be extruded into a cube shape, and a spherical portion 735 is cut with a cutting device. A blade with a rotating arc would cut the shape of a sphere. Aggregate particles 737 would be extruded and cut with a blade to produce a curved cut.
[0067] FIG. 8 includes several shapes formed by different extrusion and cutting techniques. Aggregate particle 841 will be formed when the plastic is extruded into a square and when the plastic cools it will cut and form a cube. As the hot plastic is extruded and cut, aggregate particle 843 will be formed. Faces 845 and 847 are created as the blade cuts from above and from below. The hot plastic deforms instead of cutting cleanly, which forms pointed ends, giving a diamond shape. As the hot plastic is extruded and cut, aggregate particle 851 will also be formed. Face 853 is created as the blade cuts from above. The hot plastic deforms during cutting. Aggregate particle 861 includes walls 863 surrounding hole 865. The plastic is extruded as a circle and forming a hole through the middle will be accomplished by placing a wire in the plastic. The wire is extruded with the plastic and in some embodiments, the wire is removed before the extrusion is cut. In other embodiments, the wires are cut by a blade that cuts the extruded plastic. In yet other embodiments, the holes can be formed by penetrating the aggregate plastic after the extruded plastic is cut. Holes in aggregate particles are common in bead shapes or rounded tubes, although holes can be used to increase the surface area of other aggregate particle shapes.
[0068] Other aggregate particle shapes are formed through compression molding. The extruded plastic is cut and a compression die pushes the cut pieces to form the aggregate particle shape. The compression die can form the aggregate particles into many shapes. Each half of the finned sphere aggregate particles can be formed through compression molding. Many other shapes can also be formed through compression molding.
[0069] The aggregate particles may be formed into rings and the rings are connected as in Figure 13. In some embodiments, the rings are connected in a chain. In some embodiments, the rings are connected to form a ring.
[0070] Example 3. Preparation of plastic-silica helices and fabrics. Recycled nylon 6 plastic is molded into spheres, spirals, and woven aggregate particles. The burst spheres, spirals, and wovens are designed to maximize the internal and external surface area. The source plastic was obtained from shredded homogenous nylon 6 recycled plastic waste (Direct Polymers, Denver, CO.), and the plastic was prepared for molding by mixing the recycled nylon 6 with silica in a nylon:silica ratio of 65%:35%. The nylon-silica mixture was then prepared by melting the nylon to 300-400°C, adding 2-100 microns of silica, and mixing for 10 minutes. The prepared plastic was then molded into burst spheres (Figure 4) and spirals (Figure 5) via 3D printing.
[0071] Plastic-silica helices have also been fabricated by melting nylon 6 at 300-400°C until viscous, incorporating 10-500 microns of silica into the molten mixture, and stirring for 20 minutes until homogenous. The nylon 6 with suspended silica was then shaped via extrusion at 200-400°C into plastic-silica helices with lengths of 5-25 mm and diameters of 2-20 mm.
[0072] Plastic-silica waves were also fabricated by melting nylon 6 at 300-400°C until viscous, incorporating 10-500 microns of silica into the molten mixture, and stirring for 20 minutes until homogenous. The nylon 6 with suspended silica was then pultruded into long fibers with diameters of 1-10 mm (Figure 9). The fibers can be extruded as any of the shapes used to manufacture aggregate particles. The fibers were then used to construct plastic-silica woven structures via a room temperature 3D knitting process. The fabric can be constructed with one fiber 977 in a first direction, and a second fiber 979 in a second perpendicular direction. In other embodiments, the fabric was constructed with two fibers, such as fibers 973 and 971 running in one direction, and fiber 975 running perpendicularly.
[0073] Example 4. Concrete mix with plastic molded aggregate particles. Concrete pavers (Figure 11A, Figure 11B) were constructed using a plastic aggregate particle concrete mix. Shredded homogenous nylon 6 recycled plastic waste was mixed with cement (Table 1), CaOH [equilibrium form Ca(OH)2], CO2, sand (Quikrete, model 115251), and water (Table 2). The resulting concrete mix was mixed for 10 minutes and poured into molds shaped as approximately 6" x 2.5" x 3.25" walkway pavers. The pavers molds were CO2 cured at 85-115°C and 20 PSI for 2 hours. Additional formulations for the plastic aggregate particle concrete are listed in Table 3. The samples were compression tested according to ASTM C109 / C109M standards.
[0074] The compression test results are listed in Table 3.
[0075] Example 5. Concrete mix with plastic-silica molded aggregate particles. Concrete pavers (FIGS. 11A, 11B) were constructed using the nylon-silica composite finned sphere concrete mix. An equivalent mixture (1:1:1) of the nylon-silica composite finned spheres (0.5mm:7.5mm:10mm) of Example 1 was mixed with cement, CaOH, CO2, sand, and water as described above in Example 3. The resulting concrete mix was poured into a mold, cured, and tested as described above in Example 3. Additional formulations for the nylon-silica composite finned sphere concrete are listed in Table 3.
[0076] The compressive strength of the plastic aggregate particle pavement of Example 4 was then compared to a pavement constructed with this nylon-silica composite finned sphere concrete mix of Example 4 (pavement made with the plastic-silica spheres of Example 1) (Figure 10). The compression test results are listed in Table 3. [The engineered plastic-silica molded aggregate particles outperformed the crushed plastic by approximately two times, with the ultimate compressive strength of concrete with 40% plastic-silica molded aggregate particles being 5800 versus 2900 for 40% standard, finely ground plastic. Thus, the morphology and composition of this engineering plastic allows for high compressive strength when integrated into concrete with a cement binder under CO2 curing.]
[0077] Example 6. Plastic-silica woven concrete mix. Concrete pavers and other concrete forms can be constructed with plastic fabric. Figure 12 shows multiple layers of fabric incorporated into a concrete form. The concrete is laid and the fabric is placed on top. The concrete is then poured over the fabric layers.
[0078] [Table 1]
[0079] [Table 2]
[0080] [Table 3]
[0081] Legend for Table 3: Nylon 6 (N6), non-homogeneous plastic (blend), polypropylene (PP), polyvinyl chloride (PVC), no silica (NS), custom nylon-silica aggregate (CA).
[0082] All references, including publications, patents, and patent applications cited in this specification are herein incorporated by reference to the same extent as if each reference was individually and specifically indicated to be incorporated by reference and was set forth in its entirety herein.
[0083] While the present invention has been described in particular embodiments, the present invention can be further modified within the spirit and scope of the disclosure. This application is therefore intended to cover any variations, uses, or adaptations of the invention using its general principles. Further, this application is intended to cover such departures from the disclosure as come within known or customary practice in the art to which this invention pertains and fall within the limits of the appended claims. References: 1.Saikia, Nabajyoti, and Jorge De Brito.”Use of plastic waste as aggregate in cement mortar and concrete preparation:A review.”Construction and Building Materials 34(2012):385-401. 2.Ismail, Zainab Z., and Enas A. Al-Hashmi.”Use of waste plastic in concrete mixture as aggregate replacement.”Waste management 28.11(2008):2041-2047. 3.Mohammed,Azad A.,Ilham I.Mohammed,and Shuaaib A.Mohammed.”Some properties of concrete with plastic aggregate derived from shredded PVC sheets.”Construction and Building Materials 201(2019):232-245. 4.Alqahtani, Fahad K., et al.”Novel lightweight concrete containing manufactured plastic aggregate.”Construction and Building Materials 148(2017):386-397. 5.Choi, Yun-Wang, et al.”Effects of waste PET bottles aggregate on the properties of concrete.”Cement and concrete research 35.4(2005):776-781. 6.Basha, Shaik Inayath, et al.”Mechanical and thermal properties of lightweight recycled plastic aggregate concrete.”Journal of Building Engineering 32(2020):101710. 7.Sambhaji, Patil Pramod.”Use of waste plastic in concrete mixture as aggregate replacement.”International Journal of Advanced Engineering Research and Science 3.12(2016):236956. 8. https: / / www.arqlite.com / site / construction [Explanation of symbols]
[0084] 1 Fin 3...North Pole 5. Equatorial Fin 7...space 201 Fin 203...Arctic 205 ···Equatorial Fin 207...space 301 Fin 303...North Pole 305 Equatorial Fin 411...Spherical base 413 Cylindrical protrusion 623 Aggregate particles 625 Aggregate particles 731 Aggregate particles 733 Upper pyramid section 735...Spherical part 737 Aggregate particles 841 Aggregate particles 843 Aggregate particles 845...face 847...face 851 Aggregate particles 853...face 861 Aggregate particles 863 Wall 865...hole 971 ···Textiles 973 Textiles 975 Textiles 977 ···1 fiber 979 Second Fiber
Claims
1. 1. A composition comprising: a plurality of shaped aggregate particles distributed within the cement; each shaped aggregate particle comprises a regular shape having one or more features that provide additional surface area; A composition wherein the shaped aggregate particles comprise a plastic.
2. The composition of claim 1 , wherein the plastic is a recycled plastic.
3. 3. The composition of claim 1 or 2, wherein the plastic is selected from the group consisting of PVC, HDPE, epoxy, polyester / PET, and nylon.
4. The composition of any one of claims 1 to 3, wherein the shaped aggregate particles further comprise glass fibers, glass particles, silica, or any combination thereof.
5. The composition of any one of claims 1 to 4, wherein the shaped aggregate particles comprise at least about 65% plastic.
6. The composition of any one of claims 1 to 4, wherein the shaped aggregate particles comprise from about 65% to about 75% plastic.
7. The composition of any one of claims 1 to 6, wherein the shaped aggregate particles further comprise at least 25% silica.
8. The composition of any one of claims 1 to 6, wherein the shaped aggregate particles further comprise at least 35% silica.
9. 9. The composition of any one of claims 1 to 8, wherein the regular shape is selected from the group consisting of a sphere, a cylinder, a pyramid, a cube, a spiral, an ellipsoid, a spherical burst pattern, a star, a fiber, and any combination thereof.
10. 10. The composition of claim 9, wherein the one or more features providing additional surface area are fins, ribs, twists, bends, ridges, valleys, or textures.
11. 10. The composition of claim 8 or 9, wherein the shaped aggregate particles comprise a hollow core and at least one opening capable of allowing cement to enter the hollow core.
12. 12. The composition of any one of claims 1 to 11, wherein the shaped aggregate particles have an increased surface area ratio of at least 1.2 times, at least 1.5 times, at least 2 times, at least 2.2 times, or at least 2.5 times compared to the regular shape.
13. A composition according to any one of claims 1 to 11, wherein the regular shape of the shaped aggregate particles is a sphere or an ellipsoid having a diameter of from 1 mm to 50 mm.
14. 14. The composition of claim 13, wherein the shaped aggregate particles further comprise one or more fins on an outer surface of the sphere or ellipsoid extending from the north pole and / or south pole of the sphere or ellipsoid.
15. 15. The composition of claim 13 or 14, wherein the shaped aggregate particles further comprise one or more ribs on the outer surface of the spheres or ellipsoids.
16. 14. The composition of claim 13, wherein said shaped aggregate particles further comprise one or more protrusions on said outer surface of said spheres or ellipsoids.
17. The composition of any one of claims 13 to 16, wherein the spheres or ellipsoids have a hollow core.
18. A composition according to any one of claims 1 to 11, wherein the regular shape of the shaped aggregate particles is a closed spiral.
19. 19. The composition of claim 18, wherein the closed spiral is from 1 mm to 25 mm in length, optionally from 1 mm to 10 mm in length.
20. 20. The composition of claim 19, wherein the closed spiral encloses a hollow interior space.
21. The composition according to any one of claims 1 to 11, wherein the regular shapes of the shaped aggregate particles are rods or fibers.
22. 22. The composition of claim 21, wherein the rods or fibers comprise cylindrical, triangular, rectangular, or hexagonal rods or fibers.
23. 23. The composition of claim 21 or 22, wherein the rods or fibers have a length of 1 to 1000 mm.
24. 24. The composition of any one of claims 21 to 23, wherein the rods or fibers have a diameter of from 1 mm to 100 mm.
25. The composition of any one of claims 21 to 23, wherein the shaped aggregate particles comprise a plurality of rods or fibers in an interlocking, optionally woven, structure.
26. 26. The composition of claim 25, wherein the interlocking structure is a woven structure having a weave pattern selected from one or more of a plain weave, a twill weave, a satin weave, a triaxial weave, a stitch weave, a basket weave, or combinations thereof.
27. 27. The composition of claim 25 or 26, wherein the woven structure comprises a 2D structure, a 3D structure, or a combination thereof.
28. 28. The composition of any one of claims 25 to 27, wherein the woven structure further comprises additional fibers or rods integrated in a continuous or discontinuous form.
29. A composition according to any one of claims 25 to 28, wherein the shaped aggregate particles are distributed in the composition in one or more layers.
30. The composition of any one of claims 1 to 29, wherein the shaped aggregate particles comprise from about 10% to about 50% (w / w) of the composition.
31. The composition of any one of claims 1 to 30, wherein the composition comprises about 10% to about 25% cement.
32. The composition comprises CaOH, CO 2 32. The composition of any one of claims 1 to 31, further comprising one or more of: sand, a silica by-product, and water.
33. The composition of any one of claims 1 to 32, wherein the shaped aggregate particles are randomly distributed throughout the cementitious mixture.
34. The composition of any one of claims 1 to 33, wherein the composition is molded into a final shape.
35. The composition of any one of claims 1 to 34, wherein the composition is cured.
36. 36. The composition of claim 35, wherein the composition has a compressive strength of at least 1300 PSI.
37. The composition of any one of claims 1 to 36, wherein the shaped aggregate particles comprise a plurality of different shapes.
38. The composition of any one of claims 1 to 36, wherein the shaped aggregate particles comprise a plurality of different sizes.
39. The composition of any one of claims 1 to 36, wherein the shaped aggregate particles comprise a plurality of different shapes and different sizes.
40. A walkway material comprising the composition of any one of claims 1 to 39.
41. 41. The walkway material of claim 40, wherein the walkway material is a paving material.
42. 42. The walkway material of claim 41, wherein the paver comprises one or more characteristics selected from the group consisting of a rectangular geometry, a rounded geometry, rounded corners, straight sides, tapered sides, and a logo embedded or imprinted into the paver surface.
43. 40. The composition of any one of claims 1 to 39, contained in a form selected from the group consisting of bricks, pavers, countertops, sinks, wall slabs, floor slabs, barricades, coffee tables, household items such as candlesticks and bowls, and lighting elements made of concrete.
44. A method for producing a composition according to any one of claims 1 to 39, comprising the steps of:
1. A method comprising: mixing a plurality of shaped aggregate particles with a cement mixture, the cement mixture comprising cement and one or more additional ingredients.
45. 45. The method of claim 44, wherein the shaped aggregate particles are formed by injection molding, compression molding, weaving, pultrusion, knitting, extrusion, printing, or 3D printing.
46. 46. The method of claim 44 or 45, wherein said mixing randomly distributes the shaped aggregate particles throughout the cement mixture.
47. 47. The method according to any one of claims 44 to 46, wherein the cement mixture is hardened after the mixing step.
48. 47. The method according to any one of claims 44 to 46, wherein the cement mixture is formed into a final shape and hardened after the mixing step.
Citation Information
Patent Citations
JP1974020223A
JP1974049154U
Aggregate for mortar and concrete and artificial shape aggregate as aid
JP1986215242A
Netted molded product
JP1992216749A
Deformed aggregate
JP1994321592A